Air pollution, weight loss and metabolic benefits of bariatric surgery: a potential model for study of metabolic effects of environmental exposures. Issue 5 (21st April 2017) - Ghosh, R.; Gauderman, W. J.; Minor, H.; Youn, H. A.; Lurmann, F.; Cromar, K. R.; Chatzi, L.; Belcher, B.; Fielding, C. R.; McConnell, R.
Summary: Background: Emerging experimental evidence suggests that air pollution may contribute to development of obesity and diabetes, but studies of children are limited. Objectives: We hypothesized that pollution effects would be magnified after bariatric surgery for treatment of obesity, reducing benefits of surgery. Methods: In 75 obese adolescents, excess weight loss (EWL), high‐density lipoprotein (HDL) cholesterol, triglycerides, alkaline phosphatase (ALP) and hemoglobin A1c (HbA1c ) were measured prospectively at baseline and following laparoscopic adjustable gastric banding (LAGB). Residential distances to major roads and the average two‐year follow‐up exposure to particulate matter <2.5 μm (PM2.5 ), nitrogen dioxide (NO2 ) and ozone were estimated. Associations of exposure with change in outcome and with attained outcome two years post‐surgery were examined. Results: Major‐roadway proximity was associated with reduced EWL and less improvement in lipid profile and ALP after surgery. NO2 was associated with less improvement in HbA1c and lower attained HDL levels and change in triglycerides over two years post‐surgery. PM2.5 was associated with reduced EWL and reduced beneficial change or attained levels for all outcomes except HbA1c . Conclusions: Near‐roadway, PM2.5 and NO2 exposures at levels common in developed countries were associated with reduced EWL and metabolic benefits of LAGB. This novel approach provides a model for investigating metabolic effects of other exposures.